Rab24 is required for normal cell division - Militello, Rodrigo Damián (2013)
Rab24 is an atypical member of the Rab GTPase family whose distribution in interphase cells has been characterized; however, its function remains largely unknown. In this study, we have analyzed the distribution of Rab24 throughout cell division. We have observed that Rab24 was located at the mitotic spindle in metaphase, at the midbody during telophase and in the furrow during cytokinesis. We have also observed partial co-localization of Rab24 and tubulin and demonstrated its association to microtubules. Interestingly, more than 90% of transiently transfected HeLa cells with Rab24 presented abnormal nuclear connections (i.e., chromatin bridges). Furthermore, in CHO cells stably transfected with GFP-Rab24wt, we observed a large percentage of binucleated and multinucleated cells. In addition, these cells presented an extremely large size and multiple failures in mitosis, as aberrant spindle formation (metaphase), delayed chromosomes (telophase) and multiple cytokinesis. A marked increase in binucleated, multinucleated and multilobulated nucleus formation was observed in HeLa cells depleted of Rab24. We also present evidence that a fraction of Rab24 associates with microtubules. In addition, Rab24 knock down resulted in misalignment of chromosomes and abnormal spindle formation in metaphase leading to the appearance of delayed chromosomes during late telophase and failures in cytokinesis. Our findings suggest that an adequate level of Rab24 is necessary for normal cell division. In summary, Rab24 modulates several mitotic events, including chromosome segregation and cytokinesis, perhaps through the interaction with microtubules.